The Effect of Wattpad Application on Students’ Writing Skills at SMAN 8 Padang - Puspita, Tika Aprilia; Ayudhia, Honesty Yonanda (Universitas Negeri Padang, 2024)
This research utilized a quasi-experimental research design to evaluate the effect of the Wattpad application in improving students' writing skills at SMAN 8 Padang. The research population consisted of 339 students from class X or fase E, and the researcher applied the clustered random sampling method to select the sample. Class E3 was chosen as the experimental group using the Wattpad application, while class E6 was used as the control group using conventional learning methods. For eight meetings, this research included a pre-test at the first meeting, six treatment meetings, and a post-test at the last meeting. The research instrument used recount text as the focus of analysis. The analysis data of the Independent Sample t-test show that the significance value of two tailed is 0.040, which is lower than the alpha significance of 0.05, indicating that there is a good improvement of the Wattpad application on students' writing skills.